1998
DOI: 10.1292/jvms.60.737
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Humor Dynamics in Beagle Dogs with Caffeine-Induced Ocular Hypertension.

Abstract: ABSTRACT. In order to investigate the possible mechanisms for caffeine-induced ocular hypertension, the intraocular pressure (IOP) and the outflow through the trabecular meshwork were measured in beagle dog eyes after dosing with intravenous caffeine (30 mg/kg) alone or in combination with the topical β-blocker befunolol [applied as 100 µl of a 1% (w/v) solution] which inhibits aqueous humor formation in the ciliary body. Intravenous injections of caffeine significantly increased the IOP at 0.25 and 1 hr after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
(11 reference statements)
0
7
0
1
Order By: Relevance
“…It is reasonable to believe that the effects of caffeine on the overall group were biased by that on patients with glaucoma and OHT, and to draw a conclusion on the effects of caffeine on IOP without differentiating normal individuals from patients with glaucoma or OHT is inappropriate. Caffeine has various pharmacological effects [2], and may elevate IOP by either promoting aqueous production [25] or inhibiting its drainage. In experimental animal models, caffeine acts as an adenosine receptor antagonist, which can increase intracellular cyclic AMP [2], resulting in stimulating the production of aqueous by the ciliary body and reducing the tone in smooth muscle cells of the chamber angle, leading to narrowing of the fenestrae that drainage the aqueous, and increasing resistance to the outflow of aqueous humor [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to believe that the effects of caffeine on the overall group were biased by that on patients with glaucoma and OHT, and to draw a conclusion on the effects of caffeine on IOP without differentiating normal individuals from patients with glaucoma or OHT is inappropriate. Caffeine has various pharmacological effects [2], and may elevate IOP by either promoting aqueous production [25] or inhibiting its drainage. In experimental animal models, caffeine acts as an adenosine receptor antagonist, which can increase intracellular cyclic AMP [2], resulting in stimulating the production of aqueous by the ciliary body and reducing the tone in smooth muscle cells of the chamber angle, leading to narrowing of the fenestrae that drainage the aqueous, and increasing resistance to the outflow of aqueous humor [4].…”
Section: Discussionmentioning
confidence: 99%
“…Abstracts and full texts were then reviewed further and 12 studies were weeded out. Among the 12 excluded articles, two studies were not carried out in in vivo human beings [25,26], ingestion of caffeine was not the only intervention in three articles [27][28][29], outcomes in four articles were not IOP [30][31][32][33], three articles [34][35][36] were not RCTs despite the fact that we limited the literature search to controlled trials. One of the seven eligible studies reported only the IOP at 4 hours post-intervention [37], so six trials [3][4][5][6][7][8] were finally analyzed in the meta-analysis.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Administration of that alkaloid can result in the development of pathological lesions both in eyes and in the whole body system. Kurata et al experimental studies demonstrate that caffeine induces intraocular hypertension and applied intravenously does not induce changes in aqueous humor flow through the trabeculous meshwork [19]. It has been suggested, reffering to the other investigations of those authors, that caffeine causes intraocular hypertension by inducing changes in the epithelium of the ciliary body [20].…”
Section: Discussionmentioning
confidence: 96%
“…In organ of vision caffeine causes an increase of intraocular pressure not resulting in changes in outflow through the trabecular meshwork [25], having, however, an influence on epithelial cells of ciliary body [26]. It also causes multiple decrease of ocular blood flow [27].…”
Section: Discussionmentioning
confidence: 99%